2020
DOI: 10.1364/oe.384402
|View full text |Cite
|
Sign up to set email alerts
|

Transition from purely elastic to viscoelastic behavior of silica optical fibers at high temperatures characterized using regenerated Bragg gratings

Abstract: In this study, the response of regenerated fiber Bragg gratings (RFGBs) to axial forces was investigated in a temperature range from room temperature to 900 °C. For the first time, the transition from pure elastic to viscoelastic behavior around 700 °C of a standard SMF28 optical fiber was measured with an inscribed RFBG. An elastic model with linear temperature dependencies of Young’s modulus and Poisson’s ratio was established, and showed good agreement with the measurements up to temperatures of ∼500 °C. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It has been shown that optical fibers show viscoelastic behavior under load starting at approx. 700 °C [ 9 ]. The upper temperature limit is around 1000 °C [ 10 ], where fused silica starts to devitrify, rendering the fiber unusable for optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that optical fibers show viscoelastic behavior under load starting at approx. 700 °C [ 9 ]. The upper temperature limit is around 1000 °C [ 10 ], where fused silica starts to devitrify, rendering the fiber unusable for optical applications.…”
Section: Introductionmentioning
confidence: 99%
“…They are inscribed either with a phase mask or with a point-by-point technique [43]. Both types have already been incorporated in various high-temperature and harsh environment sensing applications [17,18,22,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%